Enterobacter spp. inhibits AFB1 production in corn silage through carbohydrates competition under rust infection - Luo chongyu; Yang xin; Chen huilong; Ni chengcheng; Hou bo; Pan Lihua; Wang xiaorong; Lin yufan; Wang xuekai; Lin yanli; Ni kuikui; Dong quanmin; et al. (Chemical and Biological Technologies in Agriculture)
Abstract Background Corn rust represents a significant threat to the safety and nutritional quality of silage. Plants adjust their carbohydrate reserves to enhance disease defense mechanisms, which subsequently impacts the fermentation process of silage. However, the mechanism by which corn rust influences the microbial community and its metabolic functions in silage through carbohydrate metabolism remains unclear. This experiment aimed to investigate the effects of rust-infected corn plants from Gansu, affected by common rust, and from Hebei, impacted by southern rust, on the nutritional quality, fermentation quality, and mycotoxin levels of both raw silage materials and fermented feed. Furthermore, it sought to analyze the composition of microbial communities and the mechanisms underlying functional changes in silage using metagenomic sequencing. Results Results indicated that rust infection significantly increased the levels of water-soluble carbohydrates (WSC), yeast (YB), and molds (M) in the raw materials, which consequently led to elevated concentrations of Aflatoxin B1 (AFB1) and zearalenone (ZEN). After 6 months of ensiling, the fermentation quality improved, as evidenced by a reduction in pH and ammonia nitrogen (NH3-N%TN), an increase in lactic acid (LA) levels, and a higher lactic acid to acetic acid (LA/AA) ratio, contributing to enhanced aerobic stability. Although the contents of hemicellulose (HCEL), WSC, dry matter (DM), and lactic acid bacteria (LAB) decreased, resulting in a reduction in nutritional quality, the concentrations of mycotoxins were significantly reduced. Notably, the levels of AFB1 and ZEN in the HXB group decreased by 64.7% and 95.0%, respectively. Metagenomic analysis revealed that rust infection enriched the Pseudomonadota phylum, including Enterobacter genus. These species may inhibit AFB1 biosynthesis through carbohydrate competition. Conclusions WSC play a crucial role in the impact of rust infection on the quality of corn raw materials and silage. Rust infections in corn plants—specifically common rust in Gansu and southern rust in Hebei—resulted in increased levels of AFB1 and ZEN in the raw silage materials, alongside elevated concentrations of WSC. However, during the ensiling process, a significant quantity of WSC was utilized, contributing to the degradation of AFB1 and ZEN. Metagenomic analysis indicated that rust infection promotes the proliferation of the Pseudomonadota phylum, particularly the Enterobacter genus, which is instrumental in degrading AFB1 by competing for carbohydrate substrates. These findings provide novel insights into the relationship between crop diseases and silage quality. Graphical Abstract